Biology and Management of Hairy Bittercress (Cardamine hirsuta) in Ornamental Crop Production - Chris Marble; Shawn Steed; Nathan S. Boyd (EDIS)
Bittercress commonly grows in the potting media of container-grown ornamentals and often through drainage holes in nursery containers. It also can be a problem in propagation houses, greenhouses, and in the field. This 6-page fact sheet provides species description, plant biology, and management recommendations. Written by Chris Marble, Shawn Steed, and Nathan S. Boyd, and published by the UF Department of Environmental Horticulture, December 2014.